High Prevalence of Insufficient Vitamin D Intake and Serum 25-Hydroxyvitamin D in Chinese School-Age Children: A Cross-Sectional Study - Yan Liu (Nutrients, 2018)
Despite the importance of vitamin D in early stages of life, data are lacking on the levels of vitamin D intake and serum 25-hydroxyvitamin D (25-(OH)D) among Chinese school-age children. The aims of this study were to investigate the vitamin D intake and serum 25-(OH)D concentration of children aged 7 to 12 years in China, and to measure the associations between vitamin D status and children’s growth and development parameters. We obtained data on vitamin D intake, serum 25-(OH)D concentration, and anthropometric measurements from a cross-sectional study on school-aged children in China. Multiple linear regression and multivariable logistic regression analyses assessed the associations mentioned above. A total of 563 children (9.5 ± 1.6 years) from six areas of China were included. Among them, 86.1% had a vitamin D intake below the recommended nutrient intake (10 μg/day), and 54.7% had vitamin D deficiency (serum 25-(OH)D <15 ng/mL). We also found that high vitamin D intake was inversely associated with the risk of vitamin D deficiency (OR = 0.836, 95% confidence interval: 0.713, 0.980), and serum 25-(OH)D concentration was positively associated with the intelligence score and body mass index-for-age Z-score (BAZ) (p < 0.05). Insufficient vitamin D intake and serum 25-(OH)D are prevalent among Chinese school-aged children. A negative association was observed between vitamin D intake and the risk of vitamin D deficiency. Moreover, vitamin D status was positively associated with intelligence and BAZ, which await confirmation in future studies.